Knowledge, attitude and practices regarding basic life support among medical students of Rawalpindi Medical University, Rawalpindi - Nukhba,Noor Fatima, Mamoona Akram, Muhammad Hamza, Nukhba,Noor Fatima, Mamoona Akram, Muhammad Hamza (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Introduction: The Knowledge of Basic Life Support (BLS) is very important, especially for medical students who will become future doctors. These simple life saving maneuvers can ensure the patient’s survival and reduce morbidity and mortality. Objective: The objective of this study was to determine the level of knowledge, attitude and practice of BLS among medical students of the Rawalpindi Medical University, Rawalpindi. Methods: In this descriptive cross sectional study, medical students (3rd & 4th year MBBS) of RMU (n=376) were inquired using a self-structured questionnaire of 20 questions regarding the knowledge, attitude and practice of BLS. After excluding the incomplete response forms, the data were analyzed using SPSS v. 22.0. Results: Twenty five percent students had good, 65.7% had average and 9.3% had poor knowledge of BLS. Out of 376, 12.76% respondents were satisfied with their present knowledge. The Majority (93.08%) had a positive attitude towards learning BLS. Only 6.6% had practiced BLS and 65.69% were unable to perform CPR independently. Conclusion: Majority had an average knowledge and a positive attitude towards BLS but very few could perform it independently. This demands that the practice should go hand in hand along with its knowledge.